A case report: Maternal complications from severe dengue. What can happen? - Reny Faristin Putri Arifin; Wildan Firmansyah (Jurnal Indonesia Sosial Teknologi, 2024)
Dengue fever (DHF) is an acute infectious disease caused by dengue virus. Thrombocytopenia results from viral suppression in the bone marrow, and platelet destruction occurs. Damaged platelets worsen plasma leakage. When the amount of filtration fluid exceeds the ability and fluid trapped in the interstitium eventually enters the alveoli, there is an increase in alveolar capillaries, resulting in pulmonary oedema. The patient was referred with complaints of fever for 5 days, dizziness (+), shortness of breath (+), nausea (+), and vomiting (+). Laboratory examination showed platelets 109 x 103/µL, positive Ig G DHF Immuno Serology, and thorax X-ray with pulmonary oedema. Cesarean section and IUD insertion were performed. During and after surgery, there were no complications.